O sentido da vida e o familiar cuidador da pessoa idosa com Alzheimer - Grás, Aline Kelly Vieira Paluchowski (My University, 2020)
In the last few years, the number of families that have been confronted with the situation of having to take care of senior family members in conditions of dependence have been increasing progressively, especially when it is caused by dementia due to Alzheimer's Disease. Thus, researches that aim to deepen their results become relevant to the understanding of the theme. The present conclusion of course work has as a general goal to identify possible contributions about the meaning of life regarding the caregiver relative of the Alzheimer's Disease patient. The research proposes the following specific objectives: To characterize the phase of senior age, to conceptualize Alzheimer's Disease, to characterize the psychosocial impacts on the family caregiver's life and to conceptualize the meaning of life, according to Logotherapy. The method used was a qualitative design with an exploratory and interpretative character. The Alzheimer's Disease cultural artifact in the periphery was used as the source, in which some scenes were extracted and described, based on the objectives of the research. The instrument used was a table, and through it, the scenes of the cultural artifact were classified. The analysis framework used was the content analysis proposed by Laville and Dionne, in which the categories were defined a posteriori, using the open model. The data were interpreted qualitatively, using the matching strategy. The categories created and their respective units of analysis were: 1. Alzheimer's Disease - Cognitive decline and loss of autonomy; 2. Caregiver Relative - Impacts of the disease on the caregiver and Dependency; 3. Sense of Life - Tragedy, value of attitude and value of experience. Results: Through the analysis of the scenes of the referred documentary and the pairing with the theory it was possible to observe that Alzheimer's disease impacts in different ways on the caregiver relative's life and that before the suffering that they often manage to find a sense of life and concomitant to continue taking care of this elderly person. Even knowing that the disease is progressive and that there is no cure, the family caregiver abdicates their lives and their needs to dedicate themselves fully to the care of the elderly with Alzheimer's. Thus, the chosen artifact was fundamental to identify the contributions of the meaning of life in the family caregiver of the elderly person with Alzheimer's. [resumo fornecido pelo autor]
Nos últimos anos tem aumentado progressivamente o número de famílias que se tem confrontado com a situação de cuidar de familiares idosos em condição de dependência, principalmente quando essa é provocada por processo demencial em virtude da Doença de Alzheimer. Desse modo, estudos que busquem um aprofundamento tornam-se relevantes para compreender a temática. O presente trabalho de conclusão de curso tem como objetivo geral identificar possíveis contribuições do sentido da vida para o familiar cuidador de idosos com Alzheimer. O estudo propõe os seguintes objetivos específicos: Caracterizar a fase da velhice, conceitualizar a doença de Alzheimer, caracterizar os impactos psicossociais na vida do familiar cuidador e conceituar o sentido da vida, segundo a Logoterapia. O método empregado foi o delineamento qualitativo de caráter exploratório e interpretativo. Utilizou- se como fonte o artefato cultural Alzheimer na Periferia, no qual foram extraídas e descritas algumas cenas, com base nos objetivos do estudo. O instrumento usado foi uma tabela, e por meio dessa se realizou a classificação das cenas do artefato cultural. O referencial de análise utilizado foi a análise de conteúdo proposta por Laville e Dionne, na qual as categorias foram definidas a posteriori, usando o modelo aberto. Os dados foram interpretados de forma qualitativa, utilizando-se da estratégia de emparelhamento. Resultados: As categorias criadas e suas respectivas unidades de análise foram: 1. Doença de Alzheimer - Declínio Cognitivo e Perda de Autonomia; 2. Familiar Cuidador - Impactos da doença no cuidador e Dependência; 3. Sentido da Vida - Tríade trágica, valor de atitude e valor de vivência. Através da análise das cenas do referido documentário e o emparelhamento com a teoria foi possível observar que a doença de Alzheimer impacta de diferentes formas na vida do familiar cuidador e que é diante do sofrimento que muitas vezes ele consegue encontrar um sentido de vida e concomitante continuar cuidando deste idoso. Sabendo que a doença é progressiva e que não existe uma cura, o familiar cuidador abdica de sua vida e de suas necessidades para se dedicar integralmente no cuidado do idoso com Alzheimer. Assim, o artefato escolhido foi fundamental para identificar as contribuições do sentido da vida no familiar cuidador da pessoa idosa com Alzheimer. [resumo fornecido pelo autor]
Keywords: Psicologia; Alzheimer, Doença de; Vida - Aspectos psicológicos; Velhice - Aspectos psicológicos; Logoterapia; Idosos - Cuidado e tratamento